No evidence found for an association between prednisone dose and FVC change in newly-treated pulmonary sarcoidosis. (May 2018) - Broos, Caroline E.; Poell, Linda H.C.; Looman, Caspar W.N.; in 't Veen, Johannes C.C.M.; Grootenboers, Marco J.J.H.; Heller, Roxane; van den Toorn, Leon M.; Wapenaar, Monique; Hoogsteden, Henk C.; Kool, Mirjam; Wijsenbeek, Marlies S.; van den Blink, Bernt
Abstract: Background: Prednisone is used as first-line therapy for pulmonary sarcoidosis. What dosing strategy has the best balance between effect and side-effects is largely unknown. We analyzed change in forced vital capacity (FVC) and weight during different prednisone doses used in daily practice for treatment naïve pulmonary sarcoidosis patients. Methods: Multilevel models were used to describe FVC and weight change over time. Correlations were calculated using linear regression models. Results: Fifty-four patients were included. FVC changed over time (p < 0.001), with an average increase of 9.6% predicted (95% CI: 7.2 to 12.1) at 12 months. Weight changed significantly over time (p < 0.001), with an average increase of 4.3 kg (95% CI: 3.0 to 5.6) at 12 months. Although FVC and weight changed significantly over time, there was little correlation between prednisone dose and FVC change, while weight increase correlated significantly with cumulative prednisone dose at 24 months. In patients treated with a high cumulative prednisone dose, baseline FVC was on average lower (p = 0.001) compared to low dose treated patients, while no significant differences were observed in need for second/third-line therapy or number of exacerbations. A strategy leading to a low cumulative dose at 12 months was defined by rapid dose tapering to 10 mg/day within 3.5 months. Conclusions: These results suggest that prednisone therapy aimed at improving or preserving FVC in newly- treated pulmonary sarcoidosis can often be reduced in dose, using a treatment regimen that is characterized by early dose tapering. Highlights: No clear correlation is found between prednisone dose and FVC change in newly-treated pulmonary sarcoidosis patients. Prednisone therapy aimed at improving/preserving FVC in newly-treated pulmonary sarcoidosis can often be reduced in dose. A treatment strategy leading to a low cumulative prednisone dose was mainly defined by rapid dose tapering to 10 mg/day.